Discrete limit theorems for Estermann zeta-functions. I - Laurincikas, A.; Macaitiene, R. (Algebra and Discrete Mathematics, 2007)
A discrete limit theorem in the sense of weak convergence of probability measures on the complex plane for the Estermann zeta-function is obtained. The explicit form of the limit measure in this theorem is given.